Differences in pharmaceutical consumption and expenses between immigrant and Spanish-born populations in Lleida, (Spain): A 6-months prospective observational study - Soler-Gonzalez Jorge; Serna Maria-Catalina; Rue Montserrat; Bosch Anna; Ruiz-Magaz; Galvan Leonardo (BMC, 2008)
Abstract Background There are few studies comparing pharmaceutical costs and the use of medications between immigrants and the autochthonous population in Spain. The objective of this study is to evaluate whether there are differences in pharmaceutical consumption and expenses between immigrant and Spanish-born populations. Methods Prospective observational study in 1,630 immigrants and 4,154 Spanish-born individuals visited by fifteen primary care physicians at five public Primary Care Clinics (PCC) during 2005 in the city of Lleida, Catalonia (Spain). Data on pharmaceutical consumption and expenses was obtained from a comprehensive computerized data-collection system. Multinomial regression models were used to estimate relative risks and confidence intervals of pharmaceutical expenditure, adjusting for age and sex. Results The percentage of individuals that purchased medications during a six-month period was 53.7% in the immigrant group and 79.2% in the autochthonous group. Pharmaceutical expenses and consumption were lower in immigrants than in autochthonous patients in all age groups and both genders. The relative risks of being in the highest quartile of expenditure, for Spanish-born versus immigrants, were 6.9, 95% CI = (4.2, 11.5) in men and 5.3, 95% CI = (3.5, 8.0) in women, with the reference category being not having any pharmaceutical expenditure. Conclusion Pharmaceutical expenses are much lower for immigrants with respect to autochthonous patients, both in the percentage of prescriptions filled at pharmacies and the number of containers of medication obtained, as well as the prices of the medications used. Future studies should explore which factors explain the observed differences in pharmaceutical expenses and if these disparities produce health inequalities.